2020
DOI: 10.3390/molecules25204686
|View full text |Cite
|
Sign up to set email alerts
|

New Zileuton-Hydroxycinnamic Acid Hybrids: Synthesis and Structure-Activity Relationship towards 5-Lipoxygenase Inhibition

Abstract: A novel series of zileuton-hydroxycinnamic acid hybrids were synthesized and screened as 5-lipoxygenase (5-LO) inhibitors in stimulated HEK293 cells and polymorphonuclear leukocytes (PMNL). Zileuton’s (1) benzo[b]thiophene and hydroxyurea subunits combined with hydroxycinnamic acid esters’ ester linkage and phenolic acid moieties were investigated. Compound 28, bearing zileuton’s (1) benzo[b]thiophene and sinapic acid phenethyl ester’s (2) α,β-unsaturated phenolic acid moiety 28, was shown to be equipotent to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Directed coupling was performed with the crystal structure of the 5-LOX/NDGA complex (pdb code: 6N2W) [ 2 , 11 , 12 ], the active site of which is composed of a tetrad of catalytic residues (His-367, His-372, His-550, and Leu-673) that coordinate with the iron atom, allowing for its catalysis [ 1 , 13 ]. Conformational analysis was performed to test molecular docking in 10 conformations of 6-gingerol and 6-shogaol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Directed coupling was performed with the crystal structure of the 5-LOX/NDGA complex (pdb code: 6N2W) [ 2 , 11 , 12 ], the active site of which is composed of a tetrad of catalytic residues (His-367, His-372, His-550, and Leu-673) that coordinate with the iron atom, allowing for its catalysis [ 1 , 13 ]. Conformational analysis was performed to test molecular docking in 10 conformations of 6-gingerol and 6-shogaol.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking showed that both 6-gingerol and 6-shogaol had a high affinity for the 5-LOX catalytic pocket as they had significant interactions with two (His-367 and His-372) out of the three histidines involved in the inhibition of 5-LOX [ 1 , 2 , 13 ]. 6-Shogaol demonstrated a lower binding energy because it showed a more significant interaction with the catalytic histidines for inhibition, and demonstrated higher degrees of interaction with the residues that were involved in this catalytic pocket [ 8 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Years later, Chiasson et al [ 44 ], searching for new molecules that inhibit the 5-LOX enzyme, evaluated a series of hybrid compounds containing benzothiophene moieties and a phenolic acid fraction, which were synthesized and tested in vitro against HEK293 cells and polymorphonuclear leukocytes. The compounds with the best activity were compounds 2 and 3 ( Figure 3 ), which respectively presented IC 50 values of 6.0 µM and 6.6 µM.…”
Section: The Role Of Thiophene Derivatives In Inflammationmentioning
confidence: 99%
“…To prevent the leukotriene biosynthesis and therefore significantly intervene with the inflammatory process, there are two possibilities up to the current scientific level, (i) direct inhibition of 5-LOX for example by zileuton 11 , 12 or (ii) prevention of the 5-LOX/FLAP complex formation by FLAP inhibitors as MK-886. 9 Research has shown that direct 5-LOX inhibition can be achieved using three different methods (redox active compounds, non-redox types, and iron-ligands), 13 but to date only zileuton has received approval.…”
Section: Introductionmentioning
confidence: 99%
“…According to the latest information, it has been possible to synthesise zileuton-hydroxycinnamic acid hybrids, of which one candidate shows very promising inhibitory properties, being up to three times as active as its precursor, zileuton. 12 However the hope are on FLAP inhibitors, some of them are currently undergoing clinical trials (i.e. GSK-2190915 by Amira Pharmaceuticals and GlaxoSmithKline completed clinical phase II studies for treatment of asthma patients; licofelone by Merkle, Alfa Wassermann, and Lacer reached clinical phase III for the treatment of knee osteoarthritis [ClinicalTrials.gov]).…”
Section: Introductionmentioning
confidence: 99%